- six *(six *x^ two *cos(three *x^ two) + sin(three *x^ two)) = zero
minus 6 multiply by (6 multiply by x squared multiply by co sinus of e of (3 multiply by x squared ) plus sinus of (3 multiply by x squared )) equally 0
minus six multiply by (six multiply by x to the power of two multiply by co sinus of e of (three multiply by x to the power of two) plus sinus of (three multiply by x to the power of two)) equally zero
-6*(6*x2*cos(3*x2) + sin(3*x2)) = 0
-6*6*x2*cos3*x2 + sin3*x2 = 0
-6*(6*x²*cos(3*x²) + sin(3*x²)) = 0
-6*(6*x to the power of 2*cos(3*x to the power of 2) + sin(3*x to the power of 2)) = 0